Role of Toll-Like Receptor 4 on Osteoblast Metabolism and Function - Alonso-Pérez, Ana; Franco-Trepat, Eloi; Guillán-Fresco, María; Jorge-Mora, Alberto; López, Verónica; Pino, Jesús; Gualillo, Oreste; Gómez, Rodolfo (Frontiers in Physiology, 2018)
Inflammation is a process whose main function is to fight against invading pathogens or foreign agents. Nonetheless, it is widely accepted that inflammation takes part in multiple processes in a physiological or pathophysiological context. Among these processes the inflammation has been closely related to bone metabolism. It is well known that in systemic inflammatory diseases such as rheumatoid arthritis the inflammatory environment contributes to the reduction of the bone mineral density. This has been further evidenced in different animals models of osteoporosis where the deletion of key inflammatory molecules dramatically reduced the bone loss. On the contrary, it is also well known that certain degree of inflammation is required to allow bone fractures healing. In fact, excessive use of anti-inflammatory drugs inhibits bone fracture consolidation. The innate immune responses (IIR) contribute to the development and maintenance of the inflammation. These responses have been observed in cells of the musculoskeletal system. Chondrocytes and osteoblasts are equipped with the molecular repertoire necessary to setting up these IIR, including the expression of several toll-like receptors (TLRs). Specifically, TLR4 activation in mesenchymal stem cells (MSC), osteoblasts, and osteocytes has been involved in catabolic and anabolic process. Accordingly, in this review we have summarized the current knowledge about the physiology of TLR4, including its signaling, and its endogenous agonists. In addition we have focused on its role on osteoblast metabolism and function.